The importance of food systems and the environment for nutrition - Fanzo, Jessica (Am J Clin Nutr, 2020)
Global and local food system transformation is necessary in order to ensure the delivery of healthy, safe, and nutritious foods in both sustainable and equitable ways. Food systems are complex entities that affect diets, human health, and a range of other outcomes including economic growth, natural resource and environmental resiliency, and sociocultural factors. However, food systems contribute to and are vulnerable to ongoing climate and environmental changes that threaten their sustainability. Although there has been increased focus on this topic in recent years, many gaps in our knowledge persist on the relation between environmental factors, food systems, and nutritional outcomes. In this article, we summarize this emerging field and describe what innovative nutrition research is needed in order to bring about food policy changes in the era of climate disruption and environmental degradation.